PENGARUH TAGLINE TERHADAP BRAND AWARENESS PADA SOFTWARE INVOICE PAPER.ID - Bella Sukma; Rivaldo Rivaldo (Jurnal Pustaka Komunikasi, 2022)
Paper.id is a platform that offers convenience in managing business that can be used by UMKM to large companies. Paper.id uses a tagline which is “Software Invoice #1 in Indonesia”. However, the tagline is difficult to hear and accept in the community. So the purpose of this study is to determine the effect of the tagline on brand awareness on Paper.id invoice software. In this paper, the researcher uses a quantitative approach with data collection methods in the form of online questionnaires which are distributed to a sample of 93 people who are active users of Paper.id, especially those in the North Jakarta area. This study uses primary data, namely data from questionnaires and secondary data, namely data obtained through various literature references, namely the internet, books, journals, to articles published on the internet. This research uses advertising theory, tagline theory and brand awareness theory.The results of this study indicate the influence of the tagline on a brand awareness that is on the Paper.id invoice software by 71.8%. Paper.id and it is recommended in the future to be able to see how much influence the tagline has in advertising so that it is hoped that in the medium or long term to get more and more competitive profits and public interest.